Hand-Arm Vibration Syndrome in Occupations: Review Article - ตำหนักโพธิ มารุต; เฮงพระพรหม สรันยา (Journal of Preventive Medicine Association of Thailand, 2018)
The aim of this article is to review the literature on the prevalence and incidence of occupational hand-arm vibration syndrome or vibration induced white finger. 13 studies from 1,486 studies were included in the review; 5 studies were descriptive studies and 8 studies were analytic studies. The prevalence of hand arm vibration syndrome were 14% in construction workers, 15%, 50% and 87% in mine workers, 42.4% in forestry workers, 1% and 46% in shipyard workers, 38.2% in mechanic workers, 25.8% in agriculture workers, 91.1% in grass-cutter workers and 38% in metalworkers. The incidence of hand arm vibration syndrome were 38% in forestry workers and 21.6% in forestry and marble workers. Each study used different hand tools and different diagnostic criteria, so the results were quite different. Many Thai workers expose to hand-arm vibration, so hand-arm vibration syndrome is worth studying in Thailand.